A fast and efficient polymerase chain reaction-based method for the preparation of in situ hybridization probes - Ghafoory, Shahrouz; Breitkopf-Heinlein, Katja; Li, Qi; Dzieran, Johanna; Scholl, Catharina; Dooley, Steven; Wölfl, Stefan (Histopathology, 2012)
Ghafoory S, Breitkopf-Heinlein K, Li Q, Dzieran J, Scholl C, Dooley S & Wölfl S (2012) Histopathology 61, 306-313 A fast and efficient polymerase chain reaction-based method for the preparation of in situ hybridization probes Aims: In situ hybridization (ISH) is the method of choice for analysis of the local distribution of gene expression in tissue samples at the cellular level. In this study we present a rapid and efficient protocol for the generation of labelled cRNA probes. Methods and results: The protocol is based on the preparation of DNA in vitro transcription templates using polymerase chain reaction (PCR), using primers that include RNA polymerase promoter sequences and size-based purification of PCR fragments containing the target gene-specific cDNA and promoter elements for T7 and SP6 RNA polymerase. The optimized purification protocols ensure high transcription efficiency and target specificity of the labelled cRNA. The cRNA hybridization probes obtained are compatible with established in situ hybridization protocols. Conclusions: Purified PCR fragment-based in vitro transcription enables preparation of in situ hybridization probes which allow the rapid detection of gene expression distribution in tissue slices from any gene of interest.